Frequency and Pattern of Anterior Crossbite With Primary and Mixed Dentition in School Children - Muhammad Noman; Nayha Enver; Gulsana Hashmi; Aneeqa Yaqub; Usman Zaheer; Syed suleman Shan (Gandhara University, 2023)
OBJECTIVES To determine the frequency and pattern of anterior crossbite with primary and mixed dentition in School Children. METHODOLOGY A descriptive cross-sectional study was conducted at Sharif Medical and Dental College, Lahore. This study included 296 participants having either deciduous or mixed dentition, no history of orthodontic treatment, aged between 3-11 years, both genders and Pakistani nationals. Participants with a history of trauma, cleft lip/palate, or any craniofacial syndrome and systemic disease were excluded. Participant's age, gender, skeletal class, and anterior crossbite (ACB) were recorded. The Chi-square/Fisher exact test was run to compare ACB and their pattern among gender, age group, and skeletal class. RESULTS There is a relatively high rate of anterior crossbite in this population, which is about 10%. The females were 169(57.09%) and males were 127(42.91%). The mean age was 6.92 ± 1.68 years. Overall, the ACB was present in 31(10.47%). The most common pattern of ACB was single incisor involvement (n=11, 35.48%) followed by two incisors (n=9, 29.03%), and the least was four incisors (n=5, 16.13%). The difference for ACB was statistically significant among skeletal classes (p<0.001). The frequency of ACB was higher in skeletal class 1 (n=17, 54.84%) and in skeletal class 3 (n=13, 41.94%) than in class 2 (n=1, 3.23%). CONCLUSION The frequency of anterior crossbite is about 10%, which is relatively higher than in other populations. Most anterior cross bites are dental due to one or two incisor involvement, which can be corrected easily at the mixed dentition stage.